A prospective, multi-institutional phase II study of induction chemoradiotherapy followed by surgery in patients with non-small cell lung cancer involving the chest wall (CJLSG0801). (February 2017) - Kawaguchi, Koji; Yokoi, Kohei; Niwa, Hiroshi; Ohde, Yasuhisa; Mori, Shoichi; Okumura, Sakae; Shiono, Satoshi; Ito, Hiroyuki; Yano, Motoki; Shigemitsu, Kikuo; Hiramatsu, Yoshinori; Okami, Jiro; et al.
Highlights: The surgical results for NSCLC involving the chest wall have been unsatisfactory. A phase II study of preoperative chemoradiotherapy was conducted for those patients. Induction chemoradiotherapy followed by surgery was proven safe and effective. The trimodality therapy yielded the high rate of pathologic complete response. Abstract: Objectives: The standard therapy for patients with T3N0-1M0 non-small cell lung cancer (NSCLC) involving the chest wall is considered surgical resection and adjuvant therapy. However, the compliance of adjuvant therapy is relatively low, and the prognosis for those patients has been unsatisfactory. Therefore, we conducted a phase II study of induction chemoradiotherapy followed by surgery with the aim of improving the survival. Patients and methods: This treatment strategy consisted of induction chemotherapy (two cycles of cisplatin at 80 mg/m 2 on Day 1 and vinorelbine at 20 mg/m 2 on Days 1 and 8) concurrent with radiotherapy (40 Gy in 20 fractions) followed by surgery. The inclusion criteria were patients with resectable T3N0-1M0 NSCLC involving the chest wall who were 20–70 years of age. The primary end point was the 3-year survival, assuming an expected rate of 67%. Results: From January 2009 to November 2012, 51 eligible patients were enrolled. Induction therapy was completed as planned in 49 (96%) patients without treatment-related death, and 25 (51%) had a partial response. Complete resection combined with the involved chest wall was achieved in 46 (92%) patients, and a pathologic complete response was seen in 13 (26%) patients. Five patients experienced major postoperative complications, and 1 patient died of acute exacerbation of interstitial pneumonia. With a median follow-up period of 42 months, the 3- and 5-year overall survivals of all registered patients were 77% and 63%, respectively. There was a significant difference in the survival rate between patients with a pathologic complete response and those with a residual tumor (p = 0.039). Conclusion: The mature results of this study in a multi-institutional setting showed the treatment strategy to be safe and effective with a high rate of pathologic response for patients with NSCLC involving the chest wall.